The People Business Psychological Reflections on Management - Furnham, A. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
It is often said that business is people. The bestselling author, Adrian Furnham, draws upon psychological reflections to present a critical and challenging account of perceived wisdom and management fads. In this book he scrutinises such subjects and themes as Anxiety Management, Authenticity, the Dark Side of Gift-Giving, Modern Management Styles, Performance Appraisal Systems and Work Life Balance.